Toward Evidence-Based Practice. Issue 2 (March 2022) - Rohan, Annie; Abbu, Stephanie; Bernstein, Samantha L.; Krowchuk, Heidi V.
Abstract : Experts suggest how 6 research articles can be used in nursing practice.